2004
DOI: 10.1016/j.ghir.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

What's new in the IGF-binding proteins?

Abstract: Since their initial discovery over 25 years ago as IGF carrier proteins, the insulin-like growth factor binding protein (IGFBP) family has grown to six members, ranging in size from 216 to 289 amino acids. The assumption over the years has been that this family of proteins, having higher affinities for IGF-I and IGF-II than does the IGF-IR, serves to block access of these ligands to the receptor. Although the need for such regulatory proteins is consistent with the constitutive secretion of IGFs from many cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 99 publications
0
65
0
3
Order By: Relevance
“…IGFBPs modulate IGF functions by binding with IGFs. Recent evidence has shown that IGFBPs have dual, IGF-independent functions, including cell survival processes related to cell surface receptors and regulation of transcriptional processes involved in the cell death response and growth inhibition (Rosenzweig, 2004). The levels of IGFBP3 expression were increased in old HUVECs in vitro (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…IGFBPs modulate IGF functions by binding with IGFs. Recent evidence has shown that IGFBPs have dual, IGF-independent functions, including cell survival processes related to cell surface receptors and regulation of transcriptional processes involved in the cell death response and growth inhibition (Rosenzweig, 2004). The levels of IGFBP3 expression were increased in old HUVECs in vitro (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…After infancy, growth hormone acting through IGF-I is the main determinant of linear growth velocity (37,38). The actions of IGF-I, in turn, are modulated by a series of IGF binding proteins, principally, IGFBP-3 (39,40). Although growth-hormone expression is normal in Crohn's disease, reports (41) repeatedly have demonstrated a decreased IGF-I, with concomitant growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…In animals with disrupted IGF-1 receptor signaling, remyelination is impaired after cuprizone-induced demyelination (Mason et al, 2003). The actions of IGF-1 are tightly regulated by six high-affinity IGF binding proteins (IGFBPs), which sequester and reduce the bioavailability of IGF-1 (Pollak et al, 2004;Rosenzweig, 2004). Of relevance to myelination is IGFBP-6, because it is synthesized in the CNS, by astrocytes and OLs (Mewar and McMorris, 1997), and its decreasing levels in cultures coincide with increasing maturation of OLs (Kuhl et al, 2003).…”
Section: Introductionmentioning
confidence: 99%